"Oratia": uma metodologia para desenvolver e avaliar a habilidade oral na aprendizagem de língua assistida por dispositivos móveis - Araújo, Nathalie Rose Ramos da Fonseca (2020)
Faced with an educational reality that tends to give considerable focus to reading and writing skills, putting one of the most useful skills, oral, in the background, the present work has as its central proposal the development of a methodology, focusing on assisted language learning using mobile devices that develop and evaluate oral skills in foreign language classes. As part of this research, this new methodological perspective, Oratia, was developed, applied and validated. It is based on the recognition of students' daily lives for the creation of a meaningful didactic proposal that encourages the constant creation of mini-videos, a media that makes it possible to recognize relevant aspects of orality to be evaluated, such as the movement of the speaking apparatus, fluency, expression and pronunciation. For that, the available digital pedagogical tools were used, incorporated into the lesson plans that brought the use of minivideos as an evaluative support. For purposes of application and validation of the Oratia methodology in different educational contexts, a pilot test was carried out at a language institute, and a final intervention at a state school full time, generating proximity and possibility for the context of Brazilian Basic Education, governed by the National Common Curricular Base - BNCC (2018) which points to the development of oral skill within the school. At the end of the research, from the two application contexts, analyzing the data, such as semi-structured interviews, questionnaire and materials from the practices, it was found that the Oratia methodology is a possible strategy, adaptable and effective to what proposed, regardless of the educational scenario in which it is inserted. In addition, this research contributes to the production of knowledge regarding the use of mobile devices in the development of oral skills in a foreign language, generating the Oratia methodology as a product, included in the existing methodological repertoire of teaching and learning for development and fluid and significant assessment of orality.